Dependence of operating conditions on lifetime of Phosphor Quantum dots-based white LEDs - Singh, Preetpal; Tan, Cher Ming; Kuo, Hao-Chung; Wang, Kai; Yang, Hongchen; Lu, Rui; Hong, Jianming (My University, 2019)
Lifetime of packaged Phosphor- Quantum dot (QDs) based white LEDs is studied. Various stress parameters such as blue light luminance, temperature and moisture are considered and their effect on the performance of the Phosphor- QD based LED is investigated. The lumen degradation rate and degradation trend for LEDs is observed to be different under varying stress conditions. Lumen recovery process is also observed under light stress test.
Keywords: Light emitting diodes; Phosphor; Quantum dot; down conversion; lifetime